Impacts of the Replacement of Native Woodland with Exotic Pine Plantations on Leaf-Litter Invertebrate Assemblages: A Test of a Novel Framework. (20th December 2009) - Murray, Brad R.; Baker, Andrew C.; Robson, Tessa C.
Abstract : We present an empirical comparison of invertebrate community structure between areas of undisturbed native eucalypt woodland and areas that have been cleared and replaced with plantations of exotic radiata pine ( Pinus radiata ). Implementation of a novel conceptual framework revealed that both insect (in autumn) and arachnid (in winter) assemblages demonstrated inhibition in response to the pine plantations. Species richness declines occurred in several taxonomic Orders (e.g., Hymenoptera, Blattodea, Acari) without compensated increases in other Orders in plantations. This was, however, a seasonal response, with shifts between inhibition and equivalency observed in both insects and arachnids across autumn and winter sampling periods. Equivalency responses were characterized by relatively similar levels of species richness in plantation and native habitats for several Orders (e.g., Coleoptera, Collembola, Psocoptera, Araneae). We propose testable hypotheses for the observed seasonal shifts between inhibition and equivalency that focus on diminished resource availability and the damp, moist conditions found in the plantations. Given the compelling evidence for seasonal shifts between categories, we recommend that seasonal patterns should be considered a critical component of further assemblage-level investigations of this novel framework for invasion ecology.